Estudios preliminares de propagación in vitro de una especie endémica de Chile, Vestia foetida (Solanaceae) - Uribe, Matilde E.; Delaveau, Catherine; Paredes, Kelly; Carrasco, Pedro; Flores, Cristian (Gayana Botánica, 2012)
The in vitro germination of seeds of Vestia foetida (Ruiz et Pav.) Hoffmanns. and their multiplication was performed. A 20% in vitro germination was obtained. The best proliferation medium was MS supplemented with BAP (1.0 mg L-1) plus AIB (0.01 mg L-1), with an average of 1.7 new axillary buds per microshoot after two subcultures.